Chemical Constituents from the Fruit Peel of Goniothalamus scortechinii - Aryanti, Abdullah; Zuriati, Zakaria; Fasihuddin, Badruddin Ahmad; Laily, Din (Universiti Sains Malaysia, 2009)
The phytochemical investigation on the fruit peel of Goniothalamus scortechinii (Selayar Raja Ubat) obtained from Gunung Stong, Kelantan has resulted in the isolation of five compounds namely pinocembrine, altholactone, goniofufurone, goniotriol and goniopypyrone. Their structures were determined by extensive ultra violet (UV), infrared (IR), nuclear magnetic resonance (NMR) spectroscopy and gas chromatography-mass spectrum (GCMS) analysis.